Prenatal diagnosis of a likely pathogenic variant in ZBTB18: Natural evolution of fetal phenotype including the long bones and corpus callosum. Issue 3 (14th December 2021) - Birnbaum, Roee; Markovitch, Ofer; Biron‐shental, Tal; Kidron, Debora; Ben‐Sira, Liat; Litz Philipsborn, Shira; Reinstein, Eyal
Abstract: Pathogenic variants in ZBTB18 gene have been described only postnatally with a variable phenotypic spectrum that includes intellectual disability, microcephaly, hypotonia, poor growth, corpus callosum abnormalities, seizures, and dysmorphic facial features. These features overlap with the phenotype of 1q43‐q44 deletion syndrome (OMIM #612337). There are several genes within the 1q43‐q44 deletion region, and ZBTB18 is of particular interest due to its known involvement in neuronal differentiation and migration. We describe here a fetus presenting with an intrauterine growth restriction, diminished long bones growth, single umbilical artery, and a short corpus callosum. On mid pregnancy ultrasound, all biometric parameters including the corpus callosum were relatively small but still within the normal range. Only a targeted follow‐up during the third trimester, including neurosonographic and MRI exams, revealed the full extent of the malformation, leading to amniocentesis and a genetic workup that led to the identification of a de novo likely pathogenic variant in ZBTB18 gene. This is the first description of the evolving phenotype of a ZBTB18 ‐related disorder in a fetus, which emphasizes the challenging diagnosis of subtle findings, that mandates a high level of clinical suspicion and a targeted follow‐up throughout pregnancy.